2016
DOI: 10.1002/anzf.1189
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Violence Towards Parents – The Known and Unknowns

Abstract: Adolescent violence towards parents is one of the most poorly understood forms of family violence despite it being relatively common. This paper presents an overview of current knowledge about adolescent violence towards parents for practitioners who work with families, considering issues around definition, prevalence, impacts, and the key characteristics of perpetrators. It is concluded that both clinical and justice responses are, at present, not well informed by basic knowledge of the circumstances in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 29 publications
0
30
0
3
Order By: Relevance
“…CPV appears to most commonly occur during the adolescence of the perpetrator, though it is not limited to minors (González-Álvarez, Gesteira, Fernández-Arias, & García-Vera, 2010;Holt, 2016;Moulds, Day, Mildred, Miller, & Casey, 2016;Walsh & Krienert, 2009). Research into CPV has shown conflicting information on gender of the perpetrator, although much research suggests there to be more male perpetrators (Ibabe, et al, 2014a;Nock & Kazdin, 2002;Routt & Anderson, 2011;Walsh & Krienert, 2007).…”
Section: Research On Cpv: What Do We Know?mentioning
confidence: 99%
“…CPV appears to most commonly occur during the adolescence of the perpetrator, though it is not limited to minors (González-Álvarez, Gesteira, Fernández-Arias, & García-Vera, 2010;Holt, 2016;Moulds, Day, Mildred, Miller, & Casey, 2016;Walsh & Krienert, 2009). Research into CPV has shown conflicting information on gender of the perpetrator, although much research suggests there to be more male perpetrators (Ibabe, et al, 2014a;Nock & Kazdin, 2002;Routt & Anderson, 2011;Walsh & Krienert, 2007).…”
Section: Research On Cpv: What Do We Know?mentioning
confidence: 99%
“…It is unclear whether AVTP is best understood within the existing youth justice understandings of behaviour or is significantly different from other youth offending. Moulds et al (2016) recently reported prevalence rates of AVTP in Australia utilising police data from four States. The study determined that, within Australia, according to police reports, approximately 1–7 per cent of families are affected by AVTP, with the ‘typical’ perpetrator being a 15- to 17-year-old Caucasian young man who is generally violent towards his mother.…”
Section: Introductionmentioning
confidence: 99%
“…The focus of research to date has largely been on developing victim and offender typologies, although this has led to the identification of CPA risk factors, it has also hindered definitions of CPA and how to respond (Moulds, Day, Mildred, Miller, & Casey, 2016). Risk factors of CPA identified by prior research include gender and history of domestic violence.…”
Section: Parent Aggressionmentioning
confidence: 99%